Limits on the extension of affixal combination: structural restrictions and processing conditions - Rodrigues, Alexandra Soares (2017)
The study of the mental lexicon has been nourished by the analysis of the way complex words are mentally represented and processed. This paper concerns the syntagmatic extension of multiple affixation; specifically, the processing of complex words that contain four suffixes that operate in word-formation patterns of Portuguese. Although the individual addition of suffixes obeys structural constraints, the multiple combination results in complex words with low frequency and low expectedness by the speaker, which contribute to the lack of semantic transparency and of affixal salience of the combination. Our study demonstrates a relation between these factors and the experience of the speaker with the affixal combination, which determines the pattern character of the combination. We suggest that a suffix exerts the prediction of other suffixes as long as the combination is expected. Non-frequent heterocategorial complex words with a combination of four suffixes are contrasted with non-frequent words containing pleonastic affixation. In the latter type of words, the redundancy of semantic structures increases the semantic transparency of the word, which suggests a prediction effect operating on the semantic level of the affixal combination. Processing of complex words is dependent on the level of expectedness of the speaker towards the affix combination, which constrains the level of word acceptance by speakers.